Understanding of long-term impact of severe Traumatic Brain Injury (TBI) survivors during recovery following Intensive Care Unit (ICU) admission: a follow-up study in two neuro - center hospitals - Abdul Rashid, Nor'ain; Mohamed Ludin, Salizar; Mat Nor, Mohd Basri; Awang, Mohamed Saufi (Nursing Programme, School of Health Sciences, Universiti Sains Malaysia (USM), 2017)
Background of Study: Traumatic brain injury (TBI) is a major medical and socioeconomic problem and is the leading cause of death in children and young adults. The study concluded that subjects with severe TBI shows physical and functional improvement but remain with cognitive and psycho-social problem throughout recovery. Despite all the issues, the impact of TBI on longterm survivors in Malaysia is unknown. The aim of this study was to measure the functional level of ICU survivors’ with severe TBI within 6 months post injury. Methods: A cohort study was employed for this study. Total of 33 participants from Hospital Tengku Ampuan Afzan (HTAA) Kuantan, Pahang and Hospital Sultanah Nur Zahirah (HSNZ) Kuala Terengganu with severe TBI were included in this study. The survey of Glasgow Outcome Scale Extended (GOSE) was distributed to all samples within 6 months period. Results: The participants mean age was 31.79 and ranged from 16 to73 years old. The result of this study showed within three months after discharged from the hospital, all the participants were still poor recovery n=33 (100.0%). Meanwhile, six months after discharge from the hospital, n= 16 (48.5%) participants were scored good recovery. In this case, the SOFA and SAPS II score contributed significantly to the prediction (SOFA score p=0.045, SAPS II score p= 0.028) of functional outcomes. Conclusion: The functional outcomes of severe traumatic brain injury were improved in six months post injury. The SOFA score and SAPS II score became significant predictors for functional outcome in this study. The limitation related to this study, was small sample size and time constraint. From this study, the health care providers knew the actual conditions for severe TBI survivors’, thus; they can plan for helping the survivors’ to improve their daily life.